Cost-effectiveness of pembrolizumab with axitinib as first-line treatment for advanced renal cell carcinoma. (1st September 2020) - Bensimon, Arielle G.; Zhong, Yichen; Swami, Umang; Briggs, Allison; Young, Joshua; Feng, Yuan; Song, Yan; Signorovitch, James; Adejoro, Oluwakayode; Chakravarty, Abhiroop; Chen, Mei; Perini, Rodolfo F.; et al.
Abstract: Objective: Pembrolizumab/axitinib significantly prolonged overall survival (OS) and progression-free survival (PFS), and increased objective response rate versus sunitinib in the phase III trial KEYNOTE-426 among previously untreated patients with advanced renal cell carcinoma (RCC). This study assessed the cost-effectiveness of pembrolizumab/axitinib versus other first-line treatments of advanced RCC from a US public healthcare payer perspective. Methods: A partitioned survival model with three states (progression-free, progressed, death) evaluated lifetime costs and quality-adjusted life-years (QALYs) for pembrolizumab/axitinib and other first-line regimens: sunitinib, pazopanib and avelumab/axitinib in the overall population; and sunitinib, cabozantinib and nivolumab/ipilimumab in the subgroup with intermediate/poor prognostic risk. Costs of treatments, adverse events and medical resources were estimated. OS, PFS and treatment duration were extrapolated using parametric models fitted to KEYNOTE-426 data and hazard ratios from network meta-analyses. Utilities were derived through mixed-effects regressions of KEYNOTE-426 EuroQol-5 Dimensions-3 Levels data. Results: In the overall population, pembrolizumab/axitinib was associated with incremental cost-effectiveness ratios (ICERs) of $95, 725/QALY versus sunitinib and $128, 210/QALY versus pazopanib, and was dominant (lower cost, higher effectiveness) versus avelumab/axitinib, with incremental QALY gains of 2.73, 2.40 and 1.80 versus these therapies, respectively. In the intermediate/poor-risk subgroup, base-case ICERs for pembrolizumab/axitinib were $101, 030/QALY versus sunitinib, $6989/QALY versus cabozantinib, and $130, 934/QALY versus nivolumab/ipilimumab, with incremental QALY gains of 2.62, 1.78 and 1.06 versus these therapies. Conclusions: In this economic evaluation, pembrolizumab/axitinib was associated with higher life expectancy and QALYs and, based on typical willingness-to-pay thresholds of $150, 000–$180, 000/QALY, was found cost-effective versus other first-line treatments for advanced RCC in the US.